Adversaries on Covid-19 Set Forth an Argument Onward To Educational Endeavor: Resulting To Develop a Modular Concept in the Learning Process - Masuhay, Edilmar P. (American International Journal of Social Science Research, 2020)
The study observed on how COVID-19 disturbed the universe, its detrimental factors to detriment the constituents in particular to educational endeavor, the outcomes to teachers and to the learners. Yet, on the contrary this is also an opportune to extend teaching stratification whom a concluding scenarios that sometimes attending classes in the classrooms were insignificant not unless for formative assessment, 21st pedagogues more probably applicable whereby lectures can be done thru social media (blogs, group chats, emails). The study conveyed also that research-output-based teaching methods are more desirable as if students would be taught on how to be a writer and a researcher. However, this COVID-19 reciprocally demean traditional maneuvers hence attendance literally are not necessary, this is a resolution of vanishing the old methods of teaching but on the other hand modular concept has led to resolve the issue. This COVID-19 definitely an uprising of a new beginning onward to educational teaching stratification but subsequently this is also threatening students of which their only avenue to attain the learning process is going to internet café where they are exposed, and prohibited for safety precautions. This disease skeptically made excuses for those who were non-focus, malingered individual either to their studies or duty, this even defying one’s authority for a reason of security, a banishment of those known with infected disease, and economically the Local Government Unit (LGU) were suppressive.